DEVELOPMENT POLICY PLANNING IN GHANA: THE CASE OF HEALTH CARE PROVISION - Alatinga, Kennedy A.; Williams, John J (European Scientific Journal, ESJ, 2014)
This paper examines the historical development of health policy in Ghana within the framework of financial, geographical accessibility and the availability of health care. We find that historically, health policy has been urban biased, and largely focused on financial accessibility. Even Nkrumah’s free health care policy could not adequately address the problem of inadequate health professionals and facilities in the rural areas.The study also established that poverty is also largely a rural phenomenon.The poor benefit less from the National Health Insurance Scheme (NHIS).This situation makes the NHIS lacksocial equity, the very reason for its being. We recommend thatgovernment should expand health facilities in the rural areas, and introduce attractive incentive packages to attract and retain health professionals in such areas. And, there is an urgent need for rigorous criteria to be developed by the NHIS to identify the very poor for health insurance premium exemptions.